FUNCTIONALITY OF STUDENTS WITH PHYSICAL DEFICIENCY IN WRITING AND COMPUTER USE ACTIVITIES - Fernanda Matrigani Mercado Gutierres de Queiroz; Lígia Maria Presumido Braccialli (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
The educational inclusion is focused on the learning of all students that have confronts barriers in to effective participation in the school life. In the inclusive education perspective, the students with disabilities must meet be served preferably in the regular education and the special education that needs to offer the educational attendance specialized to complement their educational needs. In this context, the objective of the research is defined in: Describe the functionality of students with physical disabilities, in the Multifunctional Resource Rooms, for activities of writing and computer use, according to the perception of the teachers. The participants of this analysis were teachers of the Educational Service Specialist that are serving students with disabilities. For data collection was used instrument School Function Assessment. The data were organized into a single document, the categories being presented. 1)Written work; 2)Use of the computer and the equipment. The conclusion was that students with physical disabilities, especially those with impaired upper-limb functionality can have find difficult to write using conventional materials, so they need Assistive Technology to develop their writing skills. Therefore, it is important to improve the profile analysis of the student, thus to choose the more appropriate resource as, it is necessary to improve the materials of the Multifunctional Resource Rooms to meet the diversity of all students with physical disabilities, since the type of furniture, didactic-pedagogical materials and equipment, are not favor in the use by students with serious motor disabilities.